Economics Of Climate Change For Smallholder Farmers In Nepal: A Review - Pant, Krishna Prasad (Journal of Agriculture and Environment, 2013)
Climate change is taking place. It is not clear what costs the farmers face and benefit receive as the impact of the climate change. The paper assesses the costs of climate change on agriculture using literature review and deductive logic. The farmers have to bear direct and indirect costs of climate change and costs of adaptation. The direct costs involve yield decreases in crops and livestock and increase in costs of production. It also involves the costs from the increased risks of natural hazards. The indirect costs include the change in socioeconomic conditions, lost opportunities for the improvement of the living conditions and adaptation costs. Farmers are to bear heavy costs of climate change, much higher than the benefits. The benefits emerge from shortening of crop lifecycle, increase of growing seasons and carbon fertilization that increases the crop production. The study emerges with policy measures for reducing the costs of the climate change the farmers bear. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 113-126 DOI: http://dx.doi.org/10.3126/aej.v12i0.7571